Development of a Spray Pipe Evaporator for Application on Unproductive Salt Farm Land in Indonesia - Muljani, Srie; Sumada, Ketut; Pradana, Alfian Rizki; Pujiastuti, Caecilia (ASEAN Journal of Community Engagement, 2024)
This article discusses the development of a prototype spray pipe evaporator and its efficiency in producing salt in Indonesia. Due to the length of the salt harvesting season in Indonesia, many salt farmers have closed their business doors, leaving many salt ponds abandoned. The spray pipe evaporator prototype was designed to produce a brine solution with a salinity of 23–24 Be from seawater, which has a salinity of 2.5–3.5 Be, in less than 3 days. This is faster than the conventional process of a brine solution salinity of 24 Be. The prototype spray pipe evaporator was assessed in a 20 x 60 m evaporation pool with a depth of 18 cm that contained brine solution with a salinity of 15.5 Be. The number of sprays installed was 11. The salinity increased from 15.5 Be to 20.5 Be after 8.5 hr of evaporation. Meanwhile, with conventional evaporation, the salinity of the brine solution reaches 16.5 Be after 3 days of evaporation. Based on calculations of the evaporation capacity for 11 sprays, it was determined that each spray can evaporate 7.6 m3 of water. A spray pipe evaporator is thus more recommended for evaporation of seawater with a salinity of around 3–5 Be. The ratio of evaporation ponds using spray to evaporation ponds without spray is around 1:15. The technical development conducted in this study improved the evaporation process through spraying, which is applicable for salt pond farming and the salt industry. This technology arguably saves energy for pumps and reduces the number of workers, thus benefitting the salt farmers’ communities in tropical contexts, such as Indonesia.